High Diversity and Prevalence of Potentially Pathogenic Free-Living Amoebae in Water Sources from Castilla y León, Spain - Patricia Pérez-Pérez; Iván Rodríguez-Escolar; José E. Piñero; Rodrigo Morchón; Jacob Lorenzo-Morales (Pathogens)
Free-living amoebae (FLA) such as Acanthamoeba spp., Balamuthia mandrillaris, Naegleria fowleri, Sappinia pedata, Vermamoeba vermiformis and Vahlkampfia spp. are causal agents of deadly and/or disabling infections in humans. Despite recent data showing an increase in infection cases worldwide, studies on the prevalence of these emerging pathogens in water sources are scarce. Moreover, climate change is believed to facilitate the expansion and persistence of these environmental pathogens, further emphasizing the need for comprehensive surveillance. Therefore, the current study investigates the variety and abundance of free-living amoebae in different water sources in the autonomous community of Castilla y León, Spain, during different seasons of the year. Vermamoeba vermiformis was the most prevalent species and was detected in rivers, swamps, irrigation waters, swimming pools and recreational fountains. Moreover, genera such as Acanthamoeba and Naegleria and Vahlkampfia were also identified. This study highlights the diversity of FLA in the region and their relationship with local water characteristics. Given that certain FLA species are opportunistic pathogens, these results emphasize the necessity of monitoring this area and water sources.